2018
DOI: 10.26740/bisma.v1n1.p72-83
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pengembangan Sumber Daya Manusia, Budaya Organisasi dan Motivasi terhadap Kinerja Karyawan PT. Pertamina (Persero) Unit Pengolahan V Balikpapan - Kalimantan Timur

Abstract: This research aimed to analyzis effect of: 1) human resource development, corporate culture, motivation toward employee performance, 2) corporate culture toward human resource dvelopment, 3) corporate culture toward motivation, 4) motivation toward human resource development and, 5) human resource development toward motivation in PT Pertamina (Persero) Processing Unit V East Kalimantan.Furthermore, object of this research was PT Pertamina (Persero) Processing Unit V East Kalimantan. This study using survei met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Sedangkan Basrie (2018) budaya organisai yang diterapkan pada objek penelitiannya masih belum efektif. Sehingga akan berdampak pada nilai guna atau signifikansi pengaruhnya dengan kinerja karyawan.…”
Section: Berpengaruh Positif Signifikan Namun Tidak Dominanunclassified
“…Sedangkan Basrie (2018) budaya organisai yang diterapkan pada objek penelitiannya masih belum efektif. Sehingga akan berdampak pada nilai guna atau signifikansi pengaruhnya dengan kinerja karyawan.…”
Section: Berpengaruh Positif Signifikan Namun Tidak Dominanunclassified
“…The results showed that there is a positive and significant influence between organizational culture and work discipline on job performance. Research conducted by Basrie (2008) in PT Pertamina (Persero) of Processing Unit V Balikpapan stated that the effective organization of organizational culture improves the achievement of the organization. The same study conducted by Yunikewaty (2012) states that organizational culture has a positive effect on employee achievement in Oil Palm Company in Gunung Mas Regency, Central Kalimantan.…”
Section: The Influence Of Organizational Culture and Work Discipline mentioning
confidence: 99%
“…Berdasarkan studi literatur yang dilakukan pada penelitian terdahulu ditemukan kesenjangan empiris seperti penelitian (Basrie, 2018)) yang menemukan bahwa budaya organisasi tidak memiliki pengaruh pada kinerja karyawan tetapi penelitian (Pranata, 2018) yang meneliti kinerja karyawan menemukan hasil yang berbeda yaitu budaya organisasi memiliki pengaruh pada kinerja karyawan, begitupun penelitian yang dilakukan (Pranata, 2018) menemukan bahwa pengembangan sumberdaya manusia ada pengaruh pada kinerja karyawan, akan tetapi sebaliknya ada temuan yang dilakukan oleh (Fitri Anggreani, 2021), dkk (2023) pada PT. Green Global sarana tidak adanya pengaruh antara pengembangan sumberdaya manusia dengan kinerja karyawan (Hafidzi et al, 2023).…”
unclassified